2023
DOI: 10.4187/respcare.10326
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Postextubation Complications Between Positive-Pressure and Suctioning Techniques: A Systematic Review

Abstract: BACKGROUND: Several studies have investigated postextubation complications of the positivepressure and suctioning techniques; however, these studies yielded inconsistent results. Therefore, in this systematic review, we aimed to assess and compare the risk of complications between these techniques after extubation. METHODS: This study was registered with the International Prospective Register of Systematic Reviews (CRD42021272068). We searched for randomized controlled trials (RCT) or observational studies tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Two clinical trials by Andreu et al (15,16) demonstrated that using positive pressure resulted in similar clinical outcomes than using continuous suction during extubation. Recently, a systematic review on suction and positive pressure extubation was unable to conclude any recommendation and encouraged more studies to elucidate this question (17).…”
Section: Introductionmentioning
confidence: 99%
“…Two clinical trials by Andreu et al (15,16) demonstrated that using positive pressure resulted in similar clinical outcomes than using continuous suction during extubation. Recently, a systematic review on suction and positive pressure extubation was unable to conclude any recommendation and encouraged more studies to elucidate this question (17).…”
Section: Introductionmentioning
confidence: 99%